Le tecnologie emergenti: le sfide etiche della tecnoscienza - Palazzani, Laura (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
Starting from the definition of emerging/converging technologies and of enhancement and from a brief description of the main technologies, the article analyzes on a critical level the most relevant ethical theories in the pluralistic debate, the main arguments and their implications. The main conflicting schools of thought are “for” and “against” the use of these technologies, at different level. The libertarian/utilitarian theories recognise an existing right and a duty to use these technologies “beyond” therapy and towards “perfectionism” in order to improve human nature; the anti-perfectionist theories consider the search for “perfect health” as a threat to human dignity (safety and security), freedom and social justice. Special attention is devoted to the enhancement/achievement dialectic and the philosophical distinction between a quantitative consideration of strength, intelligence and emotions and their qualitative dimension, taking into account the relevance of personal and interpersonal virtues as a concrete alternative to the “biotechnological shortcut” of enhancement. Challenges to ethics and law outline the need of a new approach to governance. Keywords: Converging technologies; enhancement; achievement; governance; biolaw